Se f(x) =
Gabarito : 1
Dou 5 estrelas e obrigado para quem responder
Anexos:
Soluções para a tarefa
Respondido por
1
Resposta:
f(x)=(x-1)/(x+1) Obs...cuidado aqui x ≠-1
f((x-1)/(x+1))=-x
((x-1)/(x+1) -1)/((x-1)/(x+1)+1) =-x
{[x-1-(x+1)]/(x+1)}/{[x-1+x+1]/(x+1)} =-x
-2/(2x)=-x
-1/x=-x
1/x=x
x²=1 ==> x=-1 ou x=-1
Veja a Obs. ==> x=1 apenas
Perguntas interessantes
Ed. Física,
9 meses atrás
Português,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás